Response of wheat varieties to different nitrogen levels under dryland situations in Vertisols of Central India - Behera, U.K.; Saiprasad, S.V.; Dass, Anchal (Annals of Agricultural Research, 2016)
A field experiment comprising of four nitrogen levels viz. 0, 40, 60 and 80 kg/ha and five wheat varieties, viz., Sujata, HW 2004, HI 1500, HD 4672 (d) and A 9-30-1 (d), was conducted at Indian Agricultural Research Institute - Regional Station, Indore for, consecutive years. The experiment was laid out in randomised complete block design with split-plot arrangement. The results indicated that varieties and nitrogen levels were significantly different for grain yield, dry matter accumulation, no. of effective spikes/m2 and yellow berry incidence, while no. of grains/spike and 1000 grain weight was significantly affected by varieties only. An increase of 2 q/ha wheat yield was noticed with application of 60 kg N/ha in comparison to 40 kg N/ha; and a decline in grain yield in application of 80 kg N/ha as the nitrogen absorbing capacity of the plants was reduced due to nonavailability of moisture under rainfed conditions. An increase of 47 g/m2 dry matter accumulation was noticed from application of 60 kg N/ha in comparison to 40 kg N/ha. Bread wheat varieties viz., HI 1500, HW 2004 and Sujata showed superiority in grain yield and dry matter accumulation over durum wheat varieties. Maximum number of spikes per m2 was observed at in bread wheat variety HI 1500 with nitrogen level of 60 kg N/ha. Significant difference for yellow berry incidence was observed between the nitrogen levels and also between five wheat varieties. Application of nitrogen resulted in reduction of yellow berry incidence as compared to the control. HW 2004 produced the minimum yellow berry incidence followed by Sujata and HI 1500. It can be concluded from these results that HI 1500 is a good variety suitable for rainfed conditions and showed high nitrogen use efficiency compared to other bread and durum wheat varieties. The results showed that grain yield, dry matter accumulation, no. of effective spikes per m2, no. of grains/spike and 1000 grain weight can be improved by applying nitrogen at a dose of 60 kg N/ha under rainfed conditions, whereas, yellow berry incidence can also be reduced by applying higher doses of nitrogen.